The Potential of Solid Waste and Greenhouse Gasses Reduction in Tambak Osowilangon Material Recovery Facility in Indonesia During the Covid-19 Pandemic - Talent Nia Pramestyawati; Ponco Prasetyo; Achmad Chusnun Niam (Universitas Islam Sultan Agung, 2023)
Solid waste generation can increase due to people's activities that increase compared to the early pandemic in 2020. The solid waste management paradigm is no longer focused on landfilling waste in landfills. Solid waste reduction activities can extend the landfill's lifetime, one of the reduction activity facilities is Material Recovery Facilities (MRF). Surabaya, the capital city of East Java Province in Indonesia, has several MRF. One of them is Tambak Osowilangon . This study aims to determine the solid waste reduction in ponds in Osowilangon Material Recovery Facility during the COVID-19 pandemic and to predict greenhouse gas reduction based on solid waste. The triangular method calculates the greenhouse gases (GHG) prediction of solid waste management in Osowilangon MRF. Solid waste generation in Tambak Osowilangon MRF was produced at 2704.946 kg/day. The highest composition of solid waste was achieved by food waste (63%), and the existing reduction of solid waste in Ponds Osowilangon MRF is 56.08%. The total volume of GHG produced without reduction scenario is 6.16 x 10 6 m 3 /year, while the GHG produced from an existing reduction in Tambakosowilangon MRF is 2.4 x 10 6 m 3/ year. Solid waste management in Tambakosowilangon MRF can reduce 61.04% of the total GHG volume